Characterization of self-coloured doped zirconia for aesthetic dental application - Dr Reza Shahmiri (Elsevier, 2023)
Aim or Purpose: Co-doping of TZP ceramics with various colourant cations is investigated as a means of varying and controlling the optical properties, such as colour and translucency, of the ceramic. The chemical composition, phase composition, and microstructure of the synthesed ceramics were systematically characterised as a function of dopant type, dopant amount, and sintering conditions and are correlated to selected optical properties, to give fundamental understanding of the effect of chemical/physical characteristics of Y-TZP on its aesthetic appearance and quality. Materials and Methods: The present work aimed to examine the relevant factors of sintering temperature (1h, 2 h, 4h at 1400°C, 1500°C, 1600°C) and post-sintering annealing conditions (1 min at 750°C) commensurate with the processes of layering, which are done in two atmospheric conditions (vacuum, air). A variety of optical, microstructural, chemical, mineralogical, crystallographic, and defect chemical techniques were applied for analysis. Results: The reflected surface colour derives from the formation of a majority yellow colour centre and a minority blue colour centre. The absorbed bulk colour derives from the formation of a majority blue colour centre and a minority violet colour centre. Conclusions: Higher sintering temperatures than 1550° increase light transmission. However, vacuum firing should be avoided and firing in air optimises the colour.